An Australian Compact with the Third Sector: Challenges and Prospects - Butcher, John (Australian and New Zealand Third Sector Research Inc., 2011)
In the lead-up to the November 2007 general election, the Australian Labor Party, led by Kevin Rudd, announced its intention to repair a relationship between the Commonwealth government and the not-for-profit sector (NFPS), which it alleged had been 'broken' by the Howard government. The key policy expression of this commitment would be a 'compact' that would set the terms of engagement between the federal government, through its departments and agencies, and the NFPS. The Rudd Labor government's pursuit of a compact followed the lead of governments overseas - most notably in the United Kingdom (1998) and Canada (2001) - whose landmark agreements set the benchmarks against which most other compacts are compared. It also followed in the wake of similar initiatives by state and territory governments over the previous decade. On 17 March 2010, Prime Minister Kevin Rudd launched the National Compact. Although an important milestone, the policy journey did not end with this event. This paper explores the implementation challenges confronting government and the NFPS and considers the prospects for an Australian compact in the light of overseas and Australian experiences.